Pathological features of 78 metastatic or multicentric neoplasms involving the central nervous system in dogs - Lilian C. Heck; Fernanda G. Cony; Matheus V. Bianchi; David Driemeier; Luciana Sonne; Saulo P. Pavarini (Pesquisa Veterinária Brasileira)
ABSTRACT: Secondary neoplasms affecting the central nervous system (CNS) may occur through blood flow or direct extension. This condition occurrence has increased both due to a longer life expectancy of dogs, as well as with the employment of chemotherapeutics, which may increase the survival period and, thus, the odds of the occurrence of metastasis. The aim of this study was to analyze the epidemiological features, such as the age, breed and sex of the animals affected, as well as the gross and microscopic findings of the metastasis from neoplasms involving the CNS of 78 dogs, and, based on the data, estimate the occurrence and frequency of the metastatic or multicentric neoplasms. Females (71.79%) were most affected than males, with an average age of 9.5-years-old and a median of 10-years-old. Most of the cases had a multifocal distribution (73.07%), and epithelial neoplasms (50%) were the most common. Telencephalon was the most affected neuroanatomical region (61.1%). Mammary neoplasms were the most frequent (47.44%), followed by hemangiosarcoma (19.23%), lymphoma (10.26%) and melanoma (6.41%). Less common neoplasms included osteosarcoma, histiocytic sarcoma and lung carcinoma (2.56%). Mammary neoplasms were mainly composed of anaplastic and micropapillary carcinomas, of which only multifocal microscopic lesions were observed.